Ban, Boom, and Echo! Entrepreneurship and Initial Coin Offerings. (September 2022) - Bellavitis, Cristiano; Cumming, Douglas; Vanacker, Tom
Regulatory spillovers occur when regulation in one country affects either the expected regulatory approach and/or entrepreneurial finance markets in other countries. Drawing on institutional theory, we investigate the global implications of a regulatory spillover on entrepreneurship. We argue that regulatory spillovers have both short- and long-term effects on the number and quality of entrepreneurial finance initiatives such as Initial Coin Offerings (ICOs). Based on a large-scale sample of ICOs in 108 countries, we find that a regulatory ban of ICOs in one country causes a short-term increase in the number of low-rated ICOs in other countries and a long-term drop in the number of ICOs, especially low-rated, which increases the average ICO rating. That is, a restrictive regulation triggered a process of increased market selection.